Referendums and representative democracy [ responsiveness, accountability and deliberation - Schiller, Theo; Setealea, Maija (Routledge/ECPR studies in European political science, 2009)
Analyses how the use of referendums affects the central functions and characteristics of representative democracy. This title provides an account of the interaction between referendums and representative institutions and actors, seeking to evaluate whether referendums supplement or undermine representative democracy